Hubungan dan Peran dan kewajiban yang dimiliki oleh sekolah, keluarga, dan masyarakat dalam pelaksanaan pendidikan (Tri Pusat Pendidikan) - FANANI, AHMAD SYIHAB (Maliki Interdisciplinary Journal, 2025)
Education is a consciously planned effort carried out through a process to develop basic physical and spiritual potential in order to achieve all goals. As with education in general, it is known that education is a universal activity in human life, both in the family environment, namely parents as educators in the family and teachers Within the school setting and the community. Synergizing education in the family, school and community is very important because it can determine the psychology and behavior of students in the social life of society. For this reason, this journal will discuss education at home, And how to integrate it with education. at school and in the community..